Factors persuade individuals’ behavioral intention to opt for Islamic bank services: Malaysian depositors’ perspective - Allah Pitchay, A.; Mohd Thas Thaker, M. A.; Azhar, Z.; Amin, M.; Mohd Thas Thaker, Hassanudin * (Emerald, 2019)
Purpose: The sustainable development of Islamic banking services has motivated a significant number of depositors to choose Islamic bank services instead of the conventional bank. There are various factors that can persuade the depositors’ choice to choose an Islamic bank. This paper aims to examine the factors that persuade individuals’ behavioral intention to choose Islamic bank services. Design/methodology/approach: To achieve this objective, this study uses the theory of planned behavior (TPB) as the underlying theory to measure the factors that persuade the depositors’ behavioral intention to choose Islamic bank services. A total of 300 questionnaires were distributed to the Malaysian Islamic Bank’s depositors in Peninsular Malaysia. The data from the questionnaires were analyzed using structural equation modeling (SEM). Findings: The result showed the three variables that predicted behavioral intentions of the depositors, namely, attitude (ATT), subjective norms (SN) and perceived behavioral control (PBC), were found to be significant in persuading depositors’ behavioral intention to choose Islamic bank services. Furthermore, the findings of the study also confirmed the relevance of using TPB to measure the depositors’ behavioral intention. The results could advance knowledge in the area of Islamic finance and also have positive implications for practitioners. Originality/value: The study offers an insight into the present environment involving Islamic banking services which was established in Malaysia 30 years ago. In the context of the current study, the present environment refers to the depositors’ intention to opt for the service and the factors that influence the depositors to choose Islamic banking services apart from the religious factor which has been well acknowledged by a significant number of previous studies.